Eosinophilic oesophagitis in children: responders and non-responders to swallowed fluticasone. Issue 5 (7th February 2013) - Boldorini, Renzo; Mercalli, Francesca; Oderda, Giuseppina
Abstract : Eosinophilic Oesophagitis (EO) is characterised by large numbers of eosinophils in oesophageal mucosa in response to food or inhaled antigens. Treatment with elimination diet or corticosteroids lead to improvement in some children, but their efficacy is not optimal. Aim: of this study is to identify clinical, endoscopic and/or histological features associated with response to treatment with swallowed fluticasone propionate. Patients and methods: In the last 12 years 34 children (M/F 25/9) with EO were treated with fluticasone propionate spray 250 μg/puff by inhaler without spacer, three puffs three times a day for 6 weeks, and returned for a follow-up endoscopy. At histology 25 of them were found to be responders to therapy (73.5%) and 9 were non-responders. Anthropometric characteristics, symptoms at presentation, endoscopic and histological data at baseline between responders and non-responders were compared. Results: Age, sex, height, duration and type of main symptom at presentation, type of allergy and number of allergens, peripheral eosinophil counts an serum IgE were similar in responders and non-responders. At baseline histology findings responders had a more severe inflammation: median peak eosinophils/high power field was higher (76 vs 44 in non responders p=0.04), eosinophilic microabscesses were present in a significantly higher number of responders (p=0.04) and peak mast cells/ high power field was significantly higher (p=0.001). Conclusions: Clinical characteristics of children with EO at baseline were similar in responders and non-responders, but a more severe inflammation in oesophageal mucosa was associated with a higher response rate to fluticasone treatment.